Anemia hemolítica em bovinos de corte em sistema de criação extensivo em Mato Grosso e Rondônia - Rondelli, Leilane Aparecida da Silva (2017)
Cases of hemolytic anemia in beef cattle in a extensive breeding system in Mato Grosso and Rondônia have been monitored since 2008. The affected animals presented weakness, pale or icteric mucosas, blackened urine, prostration and anorexia. The outcome of these cases often is death, principally if the animals are forced to walk. Approximately 429 cattle died in these outbreaks andin some of these, mortality rates ranged from 0.26 to 50%. Infectious causes and some toxic causes of hemolytic anemia in bovines were investigated. After histopathological examinations, special coloring, hematology, biochemistry and molecular tests, were excluded the possible causes. Any plant ready described in Brazil as cause of hemolytic anemia in animals from livestock interest was observed in thosefarms. Although the etiology of these cases is not yet known, clinical and pathological evidences of the disease suggested that it is caused by a toxic plant of hemolytic action, present in the affected properties, but not yet confirmed experimentally.